Description of the High Ability Representation Process of Second Grade Elementary School Students in Fraction Material Based on Ethnomathematics - Imaniyah, Cahyani Dina; Fiantika, Feny Rita (Formosa Journal of Applied Sciences, 2024)
This study aims to describe the high ability representation process of second-grade elementary school students in fraction material based on ethnomathematics. Ethnomathematics connects mathematical concepts with local culture, providing students with a more concrete and relevant context for understanding the material. The research employs a qualitative method with a descriptive approach to depict findings from written representation tests, interviews, observations, and documentation. Data collection techniques include data reduction, data presentation, and conclusion drawing. The validity of the research data is tested through credibility, transferability, dependability, and confirmability. The analysis results indicate that the ethnomathematics approach is effective in enhancing students' understanding of fraction concepts. High-ability students can express mathematical concepts orally, in writing, and through drawings. They are also able to articulate their understanding through words, writing, and drawings, as well as interpret their comprehension into visual forms.